EFEKTIVITAS TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) UNTUK MENURUNKAN SKALA NYERI PADA PASIEN DYSPEPSIA DI RUANG IGD RSUD KARAWANG - Yumi Dian Lestari; Wirdan Fauzi; Tiara Puspita (Bajang Institute, 2025)
Dyspepsia is a common digestive disorder often accompanied by epigastric pain. Emotional Freedom Technique (EFT) is a non-pharmacological therapy involving tapping on specific body points combined with positive affirmations, aimed at reducing stress and pain perception. Objective: To determine the effectiveness of Emotional Freedom Technique (EFT) in reducing pain scale among patients with dyspepsia in the Emergency Department of RSUD Karawang (based on a simulated dataset of 30 patients). This study used a one-group pretest–posttest design (pre-experimental). Pain levels were assessed using the Numeric Rating Scale (NRS) before and after a 15-minute EFT session. Data were analyzed using paired t-test and Wilcoxon signed-rank test with a significance level of α = 0.05. Results: The mean pre-intervention pain score was 6.31 (SD = 0.90), and the mean post-intervention pain score was 3.22 (SD = 1.17). The average reduction was 3.09 points, with p < 0.001. The effect size (Cohen’s d = 3.69) indicates a very large effect. Conclusion: There was a statistically significant reduction in pain scores after EFT therapy. Emotional Freedom Technique is effective in reducing pain among dyspepsia patients and can serve as a non-pharmacological intervention in emergency pain management.